Modern Privacy - Blatterer, Harry. author. aut Link
VIII, 180 p.
Keywords: Modern Privacies addresses emergent transformations of privacy in western societies from a multidisciplinary and international perspective. It examines social and cultural trends in new media, feminism, law, work and intimacy which indicate that our perceptions, evaluations and enactments of privacy in constant flux.